Penguatan Pembelajaran Toleransi: Solusi Alternatif Menyiapkan Warganegara Global di Era Digital - Mahpudz, Asep (Universitas Terbuka, 2024)
The development of globalization has now been felt in various aspects of life. Currently, it has turned to digitalization in various dimensions of life, including in education. The transformation of education is increasingly important to be carried out immediately, including aspects of building awareness of educators and learners based on values, and developing culture. This article is based on a literature review. Data and information are collected from articles, manuscripts, and books related to the study. The data and information are then analyzed using the content analysis method. Efforts to explore tolerance in the aspect of cultural diversity are important, especially in multicultural countries and nations. Strengthening tolerance learning is important to develop in the context of educational transformation, digitalization of education, and preparing global citizens in the digital era. Tolerance for cultural diversity and technological adaptation should be developed in a planned and systemic manner.